Efeitos do treinamento resistido na morfologia, propriedades e marcadores de remodelamento de matriz extracelular óssea em modelo de ratas ovariectomizadas - Pisani, Graziéle Fernanda Deriggi (2016)
Absence of estrogen on menopause leads to detrimental consequences, including osteoporosis, which is characterized by unbalanced bone extracellular matrix (ECM) remodeling. Bone resistance to fracture is related to bone mass, structure and architecture including bone ECM changes. Resistance training (RT) has shown beneficial effects on prevention and treatment of osteoporosis, however, there are few studies regarding RT role in bone remodeling in different scales, such as bone composition and structure until matrix metalloproteinases (MMPs) in ovariectomy (OVX) model. Aims: To evaluate RT effects on bone properties, morphology and bone ECM remodeling markers in an OVX rat model. Methods: Thirty six female Sprague Dawley rats were divided into four groups: sham sedentary, OVX sedentary, sham RT and OVX RT. Rats performed RT for 10 weeks in which they climbed a ladder with progressive loads attached to the tails. Tibias were stored for biometrical, biomechanical, biophysical and biochemical analysis. Femurs were stored to morphological, gene expression and gelatin zymography analysis. Results: OVX decreased bone mineral density, bone mineral content, stiffness, maximal load, calcium content, trabecular number and connectivity and MMP-13 gene expression. Furthermore, OVX increased RUNX-2 and OPG gene expression and MMP-2 activity. RT was efficient in prevent or reverse almost all of alterations. Conclusion: Estrogen absence osteoporosis affects bone mass and other factors involved in bone ECM remodeling and RT showed be efficient in prevent or reverse these harmful effects.